Enhancing Customer Loyalty in Online Transportation: The Role of Price, Service Quality, Trust, and Satisfaction - Ni Ketut Tiara Astiti Nila Dewi A.; Mahir Pradana; Putu Nina Madiawati (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Customer loyalty is crucial for the long-term success of service businesses, particularly in the online transportation industry. It involves customers consistently choosing to use a company's services or products. This research seeks to examine how both pricing and service quality can influence customer loyalty within the online transportation industry by looking at factors like customer trust and satisfaction. The study utilizes a quantitative methodology with a descriptive design. The population in this study were users of K-JEK services whose number was unknown but had used K-Jek transportation services, while the number of samples was 273.25 and rounded up to 280 samples of K-Jek transportation service users. The method of collecting data involved using a survey with a Likert scale. The analysis of the data employed SEM (Structural Equation Modeling) or Structural Equation Model through the SmartPLS software. The outcomes show that Service Quality and Price impact Customer Loyalty through Customer Satisfaction and Trust. High-quality service enhances satisfaction and trust, leading to greater loyalty. Competitive pricing also improves customer perception, fostering stronger trust and retention. The findings confirm that Customer Satisfaction and Customer Trust play a crucial mediating role in strengthening these relationships. This study suggests that online transportation providers should prioritize service quality and fair pricing strategies to enhance customer loyalty. Maintaining high service standards and transparent pricing can improve customer satisfaction and trust, ultimately securing long-term success.